Managing global supply chain relationships : operations, strategies and practices - Flynn, Barbara Bechler, 1952-; Morita, Michiya; Machuca, Jose, 1949- (Hershey Pa. : Business Science Reference, 2011)
'This book focuses on issues related to relationships among members of global supply chains, addressesing three important aspects of global supply chain relationships: supply chain integration and collaboration; outsourcing and offshoring of production; and recent growth in supplier networks'--Provided by publisher.
Includes bibliographical references (p. 352-396) and index.
Keywords: Business logistics; Production management; Industrial management